Current treatment options for nodular lymphocyte-predominant Hodgkin lymphoma. Issue 5 (September 2021) - Eichenauer, Dennis A.; Engert, Andreas
Abstract : Purpose of review: Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is a rare B cell-derived malignancy. This review aims at providing an overview of recent developments in the management of NLPHL. Recent findings: Patients with stage IA NLPHL without risk factors have excellent outcomes. The 8-year progression-free survival (PFS) is roughly 90% and the 8-year overall survival (OS) close to 100% after limited-field radiotherapy (RT) alone. Individuals presenting with early stages other than stage IA without risk factors and intermediate stages have 10-year PFS rates in excess of 70% and 10-year OS rates exceeding 90% when treated with 2 and 4 cycles of ABVD, respectively, followed by consolidation RT. In advanced NLPHL, different protocols such as BEACOPP, ABVD, and R-CHOP have been evaluated retrospectively. However, the optimal approach is undefined. Patients with relapsed NLPHL mostly receive single-agent anti-CD20 antibody treatment or conventional chemotherapy. High-dose chemotherapy and autologous stem cell transplantation are restricted to high-risk patients. NLPHL recurrence is salvaged successfully in the majority of cases. Summary: Patients with NLPHL have a very good prognosis. Treatment differs from classical Hodgkin lymphoma in some situations.